Phase separation in ceramide[NP] containing lipid model membranes: neutron diffraction and solid-state NMR - Schroeter, Annett; Stahlberg, Sören; Školová, Barbora; Sonnenberger, Stefan; Eichner, Adina; Huster, Daniel; Vávrová, Kateřina; Hauß, Thomas; Dobner, Bodo; Neubert, Reinhard H H; Vogel, Alexander (Soft matter, 2017)
The stratum corneum is the outermost layer of the skin and protects the organism against external influences as well as water loss. It consists of corneocytes embedded in a mixture of ceramides, fatty acids, and cholesterol in a molar ratio of roughly 1 : 1 : 1. The unique structural and compositional arrangement of these stratum corneum lipids is responsible for the skin barrier properties. Many studies investigated the organization of these barrier lipids and, in particular, the exact conformation of ceramides. However, so far no consensus has been reached. In this study, we investigate a model system comprised of N-(non-hydroxy-tetracosanoyl)-phytosphingosine/cholesterol/tetracosanoic acid (CER[NP]-C24/CHOL/TA) at a 1 : 1 : 1 molar ratio using neutron diffraction and 2H solid-state NMR spectroscopy at temperatures from 25 °C to 80 °C. Deuterated variants of all three lipid components of the model system were used to enable their separate investigation in the NMR spectra and quantification of the amount of molecules in each phase. Neutron scattering experiments show the coexistence of two lipid phases at low temperatures with repeat spacings of 54.2 Å and 43.0 Å at a physiological skin temperature of 32 °C. They appear to be indistinguishable in the 2H NMR spectra as both phases are crystalline and ceramide molecules do not rotate around their long axis on a microsecond timescale. The evolution of these phases upon heating is followed and with increasing temperature fluid and even isotropically mobile molecules are observed. A model of the organization of the lamellar phases is proposed in which the thicker phase consists of CER[NP]-C24 in a hairpin conformation mixed with CHOL and TA, while the phase with a repeat spacing of 43.0 Å contains CER[NP]-C24 in a V-shape conformation.